A study in early neonatal period for the outcome based on the hepatic involvement following severe birth asphyxia in full term neonates - Elumalai, Sengodi; Kathavarayan, Rajasekaran; Govindasamy, Venkatesh; S., Sophiya Preethy (International Journal of Contemporary Pediatrics, 2020)
Background: The current study is focused on assessing the liver involvement of severely birth asphyxiated newborns, by measuring liver enzymes like Serum glutamic oxaloacetic transaminase (SGOT) and Serum glutamic pyruvic transaminase (SGPT) to predict the outcome of those babies. Methods: Total 111 severely birth asphyxiated newborns were assessed in a hospital based prospective analytical study. Liver enzymes were measured for all babies included in the study. Study subject details were obtained through a pre-structured questionnaire and also morbidity and mortality were noted. Analysis of the research data was done through appropriate statistical methods using SPSS version 20. Results: It was observed that incidence of hypoxic ischemic hepatitis, among entire study population was 34.2% (38 cases) based on SGPT (>100 U/l) values. Current study findings indicated that incidence of hypoxic ischemic hepatitis had a positive correlation with hypoxic ischemic encephalopathy (HIE) staging. Mean SGOT, SGPT values were observed to increase as the HIE staging progressed. Based on Spearman’s correlation coefficient evaluation, it was determined that the elevated SGOT and SGPT values had moderate positive correlation with HIE, seizure, ventilator support and death in the study population. It was found from the present study findings that statistically significant mortality (77.4%) was observed among the HIE stage III babies, with elevated SGPT values. Conclusions: Current study findings revealed that elevated SGOT and SGPT values (more than twice the normal) has high sensitivity to predict the outcome in severely birth asphyxiated newborns. The stated parameters can prove to be effective in counselling parents regarding morbidity and mortality of neonates due to birth asphyxia.